1998
DOI: 10.1172/jci1378
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthesis in the lung. Regulation by oxygen through a kinetic mechanism.

Abstract: In this study, we show that oxygen regulates nitric oxide (NO) levels through effects on NO synthase (NOS) enzyme kinetics. Initially, NO synthesis in the static lung was measured in bronchiolar gases during an expiratory breath-hold in normal individuals. NO accumulated exponentially to a plateau, indicating balance between NO production and consumption in the lung. Detection of NO2-, NO3-, and S-nitrosothiols in lung epithelial lining fluids confirmed NO consumption by chemical reactions in the lung. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
203
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(217 citation statements)
references
References 46 publications
9
203
2
3
Order By: Relevance
“…The reported K m of NO synthase for O 2 varies widely, from 6-23 M (37) up to 135-400 M (38). However, in our hands S-EITU was able to inhibit NO release even when given at an [O 2 ] as low as 10 M, indicating that NO synthase remains active in the cells at very low [O 2 ].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The reported K m of NO synthase for O 2 varies widely, from 6-23 M (37) up to 135-400 M (38). However, in our hands S-EITU was able to inhibit NO release even when given at an [O 2 ] as low as 10 M, indicating that NO synthase remains active in the cells at very low [O 2 ].…”
Section: Discussioncontrasting
confidence: 46%
“…We refer to both these situations, an accumulation of electrons at cytochrome a or an increase in reduced species at the catalytic center, as cytochrome c oxidase becoming more reduced. (37,38,49).…”
Section: Simultaneous Measurement Of Cytochrome Redox States [O2] Andmentioning
confidence: 99%
“…1) Exhaled NO does not increase after experimental elevation of cardiac output (12). 2) Exhaled NO is decreased on acute exposure to high altitude, despite elevation of cardiac output (11,23,30).…”
Section: Discussionmentioning
confidence: 97%
“…Other things being equal, higher cardiac output might even lower NO if it causes recruitment and perfusion of blood vessels in which NO output could be scavenged by circulating hemoglobin, instead of being exhaled. NO delivery from the circulation to the lung is discounted, because hemoglobin inactivates NO (21) and because direct measurement of bronchiolar gases showed that alveolar NO was virtually nil (12,24).…”
Section: Discussionmentioning
confidence: 99%
“…[31]). It includes transcriptional [32], translational and posttranslational [33][34][35] regulations of NO-synthesis mechanisms, negative feedback regulation of NOS by NO [36][37][38][39], membrane transport of substrates [40][41][42][43], intracellular metabolic recycling of substrates [43][44][45][46][47][48][49][50][51], availability of molecular oxygen and cell respiration [52][53][54][55][56][57], and intracellular redox state [58][59][60].…”
Section: No Productionmentioning
confidence: 99%